A study on relation between social media dependency and loneliness among Malaysian Universities student - Khaw, En Qi (2024)
Social media refers to digital technologies that prioritise user-generated material or interaction (Carr & Hayes, 2015). There are several platforms like Facebook, Instagram or Whatsapp, which bring convenience and interaction to society. Social media has become more popular among youngsters like university students. So, in this paper I am going to study the relationship between social media addiction and loneliness among university students. The survey question will be using a quantitative method to collect the data from 50 university students to study their addiction level on social media and why they feel loneliness. In the result, a random sample (S=50) of males (m=20) and females (l=30) who are university students from different universities have participated in the survey to provide their opinion on how social media addiction affects loneliness among the students. There are 60% of students show the results that social media has become their primary platform to connect with others where they feel loneliness when using it, and 40% of them might think differently. Hence, the result indicates that spending more time on social media and becoming addicted will have negative aspects on university students.